Cost of production estimates for wheat, milk and pigs in selected EU member states - Werner Kleinhanß; Frank Offermann; Jean-Pierre Butault; Yves Surry (Johann Heinrich von Thünen-Institut (vTI), 2011)
This study summarizes cost estimates based on the EU Farm Accountancy Data Network using the General Cost of Production Model, developed, applied and tested within the FACEPA project. Results are provided for wheat, pigs and milk for the main producer countries of the EU for the period 1999 to 2007. Estimated input-output coefficients are generally based on monetary figures, expressing cost shares referring to total output. Effects of scale, specialization and location can be derived by estimates based on respective sub-samples. Costs per unit are derived based on input-output coefficients and output values, providing costs per hectare or ton for wheat and per ton of milk. There is a considerable variation between Member States not only of production costs, but also of output, and output plus subsidies (due to the national implementations of full or partially decoupling schemes), especially for wheat and milk.
urn:nbn:de:gbv:253-201112-dn049633-0
Keywords: C39; Q12; 630; econometric analysis; production costs